UWB Signals, SA Perspectives in Radar Guidance - Sachuk, I.I.; Orlenko, V.M.; Shirman, Y.D. (The third international conference, ultrawideband and ultrashort impulse signals : UWBUSIS 2006, September 19-22, 2004, Sevastopol, Ukraine, 2006)
Now, active or semiactive guidance of antiair missile is commonly implemented using narrowband radar illumination signals. But the usage of wideband signals and inverse aperture synthesis for that purpose can give the new capabilities to the target tracking and missile guidance algorithms. Some simulation results are given in confirmation of that statement